Fog and low stratus over the Swiss Plateau − a climatological study. (16th May 2013) - Scherrer, Simon C.; Appenzeller, Christof
ABSTRACT The occurrence of fog and low stratus (FLS) clouds is a common phenomenon over the Swiss plateau during the winter half years. Classical fog observations using horizontal visibility are of limited use for climatological analyses of persistent FLS situations. We present a simple method for determining long climatological series of days with FLS lasting at least a half or a full daylight day. The method relies solely on high quality relative sunshine duration measurements at two stations, a Plateau station below or within the FLS layer (e.g. Zürich/Fluntern) and a nearby peak station above the FLS layer (e.g. Säntis). The analysis for the period 1901–2012 shows that full day FLS are a typical phenomenon of the months November to January, whereas the half day FLS also often occur in October and February. There is substantial interannual and decadal variability. The total number of Zürich full FLS days varies between 4 and 31 d (mean: 17 d) and between 10 and 49 d (mean: 28 d) for at least a half FLS days in the September to March period. The foggiest decade in the 1901–2012 record was 1984–1993; the least foggy decade was 1999–2008 with roughly 40–45% less FLS occurrence than only 15 years before. In the most recent years a return towards the climatological mean can be observed. The long term data series does not show any significant long‐term trends for the occurrence of full nor for half day FLS events. The reconstructed FLS occurrence is well correlated with the number of days with cold air pooling. They show very similar decadal variability and long term trends. © 2013 Royal Meteorological Society